(untitled) (Journal of Economic Research & Business Administration, 2016)
In this article, develop a model of dynamic stochastic general equilibrium of multiple countries is developed. The indicators of output, interest rate, inflation, exchange rate, terms of trade for each country, as well as exports, and imports for each pair of countries are considered. The model contains equations of dynamic IS and New Keynesian Phillips curves and equations of monetary policy corresponding to the number of countries. The estimation of the model was implemented for the economies of Kazakhstan, Russia and the EU. An asymmetrical interaction of large and small economies was taken into account. The analysis of the impact of internal and external shocks on the macroeconomic variables is performed for each country/region.